Magnetic molecularly imprinted polymers for selectively adsorbing flavins and their effects on bioremoval of Acid Red 18 and Cr(VI). Issue 8 (11th April 2022) - Liu, Xinxin; Lu, Hong; Li, Qiansheng; Fu, Ze; Tan, Feng; Wang, Xiaolei; Zhou, Jiti
Abstract: BACKGROUND: Flavins can be used as redox mediators to accelerate anaerobic biotransformation of refractory pollutants. For better application of flavins, suitable immobilization methods need to be developed. As most microorganisms can synthesize flavins, it is a good strategy to develop selective solid sorbents for immobilizing the flavins released by waste biomass including waste activated sludge (WAS). RESULTS: Novel core–shell magnetic molecularly imprinted polymers (MMIPs) for flavins were successfully prepared. The adsorption amount of 10 mg of MMIPs for flavin mononucleotide (FMN) could reach 29.19 μmol g −1, which was around 24.9‐fold higher than that of magnetic non‐molecularly imprinted polymers (1.17 μmol g −1 ). Their isothermal adsorption process followed the Langmuir model. Similar adsorption behaviors of MMIPs were also observed for flavin adenine dinucleotide (FAD) and riboflavin. The three flavins adsorbed on MMIPs enhanced the removal rates of azo dye Acid Red 18 (AR 18) and Cr(VI) by Shewanella oneidensis MR‐1. Moreover, the catalytic performance of MMIPs–FMN could remain at 97.6% of the original value after five repeated usages. Further studies found that MMIPs could efficiently adsorb FAD from the lysate of WAS, and MMIPs–FAD enhanced the decolorization of AR 18. CONCLUSIONS: The novel MMIPs could selectively adsorb flavins. MMIPs–flavins exhibited good catalytic and repeated usage performances, indicating that they could be used for accelerating anaerobic biotransformation of refractory pollutants. © 2022 Society of Chemical Industry (SCI).